Vascular considerations in foot and ankle free tissue transfer: Analysis of 231 free flaps. Issue 4 (23rd March 2015) - Cho, Eugenia H.; Garcia, Ryan M.; Pien, Irene; Kuchibhatla, Maragatha; Levinson, Howard; Erdmann, Detlev; Levin, L. Scott; Hollenbeck, Scott T.
Abstract : Objective: Successful foot and ankle soft tissue reconstruction is dependent on a clear understanding of the vascular supply to the foot. The aim of this study was to identify risk factors for reconstructive failure following foot and ankle free tissue transfer. Methods: The authors retrospectively reviewed their 17‐year institutional experience with 231 foot and ankle free flaps performed in 225 patients to determine predictors of postoperative foot ischemia and flap failure. Postoperative foot ischemia was defined as ischemia resulting in tissue necrosis, separate from the reconstruction site. Results: Six (3%) patients developed postoperative foot ischemia, and 28 (12%) patients experienced flap failure. Chronic ulceration ( P  = 0.02) and an elevated preoperative platelet count ( P  = 0.04) were independent predictors of foot ischemia. The presence of diabetes was predictive of flap failure ( P  = 0.05). Flap failure rates were higher in the setting of an abnormal preoperative angiogram ( P  = 0.04), although the type and number of occluded arteries did not influence outcome. Foot ischemia was more frequent following surgical revascularization in conjunction with free tissue transfer and the use of the distal arterial bypass graft for flap anastomosis ( P  < 0.01). Overall, no differences were observed in foot ischemia ( P  = 0.17) and flap failure ( P  = 0.75) rates when the flap anastomosis was performed to the diseased artery noted on angiography, compared with an unobstructed native tibial artery. Conclusions: Foot and ankle free tissue transfer may be performed with a low incidence of foot ischemia. Patients with diabetes, chronic ulceration, and an elevated preoperative platelet count are at higher risk for reconstructive failure. © 2015 Wiley Periodicals, Inc. Microsurgery 36:276–283, 2016.